2021
DOI: 10.1159/000511249
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib-Induced Acute Liver Failure

Abstract: Drug-induced liver injury is an uncommon but life-threatening entity. Sunitinib is a tyrosine kinase inhibitor used for advanced and imatinib-refractory gastrointestinal stromal tumors. It causes transient elevation in liver enzymes. The incidence of fatal acute liver failure is rare. Five cases of sunitinib-induced acute liver injury have been reported in the literature thus far. We present a case of fatal acute liver failure and cardiomyopathy within 2 weeks of sunitinib therapy initiation for advanced pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Meta-analysis indicated safety and limited benefit regarding prolongation of patient survival with native liver without transplantation and survival after transplantation however, with no improvement of overall survival [ 70 ] NAC significantly reduces the level of reactive oxygen species produced by sunitinib and crizotinib and reduces sunitinib- and crizotinib-induced mitochondrial apoptosis and cellular damage. The use of NAC has been reported in several case reports of fulminant acute liver failure associated with TKIs [ 17 , 71 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis indicated safety and limited benefit regarding prolongation of patient survival with native liver without transplantation and survival after transplantation however, with no improvement of overall survival [ 70 ] NAC significantly reduces the level of reactive oxygen species produced by sunitinib and crizotinib and reduces sunitinib- and crizotinib-induced mitochondrial apoptosis and cellular damage. The use of NAC has been reported in several case reports of fulminant acute liver failure associated with TKIs [ 17 , 71 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fulminant liver failure associated with sunitinib treatment is rare. Several cases of serious sunitinibinduced acute liver failure, including fatal cases, have been reported in the literature [17][18][19][20][21][22]. A meta-analysis of 3691 patients focusing on the incidence and relative risk of liver injury in patients treated with anti-angiogenic TKIs found that liver injury of sunitinib, pazopanib or other anti-angiogenic TKIs did not depend on the type of disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…As of October 2019, the FDA has approved 53 small molecule kinase inhibitors, seven (sunitinib, lapatinib, pazopanib, regorafenib, ponatinib, idelalisib, pexidartinib) of which had a black box warning of liver toxicity, and twenty-nine of which had warnings and precautions for hepatotoxicity in their product labeling (26). Many case reports demonstrated that crizotinib and sunitinib induced hepatotoxicity, even acute liver failure (ALF) (27)(28)(29). However, dose adjustment or drug discontinuation are the common strategies to reduce or manage hepatotoxicity induced by crizotinib or sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…individual patients [33,34]. As most of TKIs are metabolized by hepatic cytochrome P450 enzyme system, clinicians should be aware of potential hepatotoxicity with TKIs in patients with liver dysfunction.…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…In order to overcome the necessity for separation and washing steps of the filtration binding assay, the "mix and read" scintillation proximity assays were developed [49]. Reaction Biology Corporation's 33 PanQinase™ is an example of a scintillation proximity assay whereby the reaction with [ 33 P]-ATP is performed using microtiter plates coated with scintillant for detection [50]. A variety of radio isotypes can be utilized in a scintillation proximity assay [49].…”
Section: Scintillation Proximity Assaymentioning
confidence: 99%